Occurrence of Salmonella in drinking water samples of urban water supply system of Kathmandu - Shrestha, Esha; Bhatta, Dwij R; Lekhak, Binod (Botanica Orientalis: Journal of Plant Science, 2010)
Water-borne diseases are among the leading causes of morbidity and mortality in developing countries and around 2.2 million people die every year due to basic hygiene-related diseases, like gastroenteritis, diarrhea, typhoid and dysentery. Eighty-six water samples were randomly collected from urban water supply system of Kathmandu, and analyzed for physiochemical and microbiological parameters to assess drinking water quality. Residual chlorine was undetectable in 100% samples. Salmonella was detected in 4 samples by enrichment culture technique in Selenite F broth followed by plating on Salmonella-Shigella Agar. A total of 10 isolates were identified as Salmonella (S. Paratyphi, 10% and non-typhi, 90%) by conventional biochemical test. The majority of the isolates were susceptible to most of the antimicrobials tested; however, resistance was observed to amoxicillin (70%), cephalexin (20%) and ceftizoxime (14.28%). There was no significant relationship between coliform and Salmonella positivity (P = 0.366). The microbiological quality of urban water supply system is poor and indicates chances of outbreak of Salmonella infection. Key-words: drinking water quality; Nepal; water-borne disease; water pollution. DOI: 10.3126/botor.v6i0.2911 Botanica Orientalis - Journal of Plant Science (2009) 6: 52-55